Application of the Singing Method to Increase Children Arabic Vocabulary at the Tahfizh Markazul Qur'an House in Nagari Panyalaian - Wahyuni, Sisri; Husna, Maratul; Suharmon, Suharmon (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Applying the singing method to help children learn Arabic is an innovative approach that aims to improve children's language skills in a fun and effective way. This method uses simple songs with easy-to-remember lyrics to introduce new vocabulary, sentence patterns and Arabic intonation. Through repetition of songs, children can learn Arabic naturally, strengthen memory, and improve listening and speaking skills. Additionally, singing supports children's social and emotional development by creating a more interactive and collaborative learning environment. Songs that contain positive values can also introduce Arab culture and teach moral values that are important in building children's character. Teachers hope that this fun approach can help children learn Arabic more holistically, while developing an interest and love for Arabic language and culture. This research aims to determine the benefits of using the singing method in children's Arabic language learning and its impact on the learning process. The aim of this research is to examine the application of the singing method in children's Arabic language learning and to determine the benefits obtained from using this method. This singing method has been proven to improve children's Arabic language skills in terms of listening, pronunciation, mastery of natural vocabulary and sentence structure. In addition, singing activities improve the development of social and emotional skills as well as children's motivation to learn. Through songs that contain moral messages and Arabic cultural values, children are also introduced to aspects of Arabic culture and traditions, thus deepening their understanding of the language they are learning. This research uses a qualitative approach through observations and interviews with teachers and students who use the singing method to learn Arabic. The research results show that this method is effective in accelerating children's learning process, increasing their confidence in communicating, and strengthening their memory for lesson content. Therefore, using the singing method when learning Arabic can be an effective and fun alternative in teaching this language to children.